Admission control algorism study of multi-rate traffics for TD-SCDMA system - Fang-wei LI; Han LI; Xiao LU (Tongxin xuebao)
A call admission control strategy based on traffic priorities was proposed after considering the different rates of traffic requirements and the attributes of different admission requests of services.According to the current system load ,it decides whether or not to accept the call request by taking the strategy of queue / deceleration / demolitions.Simulation results show that the strategy is significantly improved in the systems service level and resource utilization.